2006
DOI: 10.1097/01.ta.0000221350.64301.6e
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Model for the Treatment of Lethal Bleeding Injury to the Juxtahepatic Vena Cava With Stent Graft

Abstract: We developed an experimental dog model of endovascular lethal injury of the JHIVC with significant increase in abdominal pressures, and a mortality rate of 100%. The treatment of this lesion with SG resulted in a thickened neointima layer, and a 27% reduction in the JHIVC lumen diameter, without clinical repercussion, and with a 100% survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…34 Perhaps most exciting is the application of stent grafts in the venous system. 35,36 One particularly challenging venous injury remains, the retrohepatic vena cava injury. In an effort to investigate the application of stent grafts for the treatment of this injury, Porta et al 35 developed a canine model of vena cava injuries.…”
Section: Endovascular Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Perhaps most exciting is the application of stent grafts in the venous system. 35,36 One particularly challenging venous injury remains, the retrohepatic vena cava injury. In an effort to investigate the application of stent grafts for the treatment of this injury, Porta et al 35 developed a canine model of vena cava injuries.…”
Section: Endovascular Approachmentioning
confidence: 99%
“…35,36 One particularly challenging venous injury remains, the retrohepatic vena cava injury. In an effort to investigate the application of stent grafts for the treatment of this injury, Porta et al 35 developed a canine model of vena cava injuries. In this study, the authors demonstrated technical feasibility as well as 100% survival for animals rescued with stent graft placement after endovascular injury of their inferior vena cava.…”
Section: Endovascular Approachmentioning
confidence: 99%
“…Other types of shunts were successful. Porta et al 9 used the stent graft for the treatment of JHC injuries in dogs, and Watarida et al 10 reported successfully using a fenestrated stent graft in a patient with an RHC injury. These cases suggest that the stent graft may be practical for treating this type of injury.…”
mentioning
confidence: 98%